2002
DOI: 10.5194/hess-6-927-2002
|View full text |Cite
|
Sign up to set email alerts
|

Simplicity versus complexity in modelling groundwater recharge in Chalk catchments

Abstract: Models of varying complexity are available to provide estimates of recharge in headwater Chalk catchments. Some measure of how estimates vary between different models can help guide the choice of model for a particular application. This paper compares recharge estimates derived from four models employing input data at varying spatial resolutions for a Chalk headwater catchment (River Pang, UK) over a fouryear period (1992)(1993)(1994)(1995) that includes a range of climatic conditions. One model was validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…This would suggest that all flow occurs in the matrix (Wellings, 1984). However, annual rainfall represents a summation of events of intensities ranging (Grindley, 1969) (a simple soil moisture accounting model) to derive a recharge flux from precipitation data (Rushton et al, 1989;Ragab et al, 1997;Bradford et al, 2002). Andrews et al (1997) used recharge data derived from the Penman-Grindley model as the driving flow for a simple solute transport model.…”
Section: History Of Chalk Unsaturated Zone Modelsmentioning
confidence: 99%
“…This would suggest that all flow occurs in the matrix (Wellings, 1984). However, annual rainfall represents a summation of events of intensities ranging (Grindley, 1969) (a simple soil moisture accounting model) to derive a recharge flux from precipitation data (Rushton et al, 1989;Ragab et al, 1997;Bradford et al, 2002). Andrews et al (1997) used recharge data derived from the Penman-Grindley model as the driving flow for a simple solute transport model.…”
Section: History Of Chalk Unsaturated Zone Modelsmentioning
confidence: 99%
“…In contrast, limitations of water balance models, as equivalence of shallow infiltration and recharge (Flint et al, 2002), can be easily assumed for shallow aquifers present on fractured bedrock, while strengths as spatial and temporal distributions of recharge are desirable capabilities of the modeling approach. Furthermore, where land uses and soil types are relatively uniform and limited data determines the choice of model, simple models provide a reasonable basis for long-term recharge estimates at the catchment scale compared to complex distributed models (Bradford et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating recharge rates in arid areas is particularly difficult, and at the same time extremely important as rainfall is scarce and infrequent. Several recharge studies have shown strong correlation between annual precipitation and the amount of recharge (Bradford et al 2002;Döll and Fiedler 2008) yielding a general perception that more rainfall will result in more recharge and consequently aquifer replenishment. Infiltration rate, however, varies with the type of soil cover, degree of initial moisture content, intensity and duration of the rainfall, depth to the water table and aquifer effective porosity, and conductivity.…”
Section: Introductionmentioning
confidence: 99%